METHOD FOR SYNTHESIS OF INFORMATION MODEL OF COMBAT SITUATION - D. I. Rabchonak (Informatika)
The technique of structural and parametric synthesis of the information model of the combat situation on the workstation of the decision maker is considered. The used method of diagonal matrix of events allows to form an effective structure, parameters and connections between the elements of the information model. The prototypes of dynamic elements of the information model are developed. The adequacy of the information model is tested. The effectiveness of the information model using the integral index of the quality of the human operator work is evaluated.